Responses of Photosynthetic and Defence Systems to High Temperature Stress in Quercus suber L Seedlings Grown under Elevated CO2 (Plant biology (Stuttgart, Germany), 2008)
Growth in elevated CO2 led to an increase in biomass production per plant as a result of enhanced carbon uptake and lower rates of respiration, compared to ambient C02-grown plants. No down-regulation of photosynthesis was found after six months of growth under elevated CO2. Photosynthetic rates at 15°C or 35°C were also higher in elevated than in ambient C02-grown plants, when measured at their respective CO2 growth condition. Stomata of elevated C02-grown plants were less responsive to temperature as compared to ambient CO2 plants. The after effect of a heat-shock treatment (4 h at 45°C in a chamber with 80% of relative humidity and 800—1000 tmol rn2 photon flux density) on Amax was less in elevated than in ambient C02-grown plants. At the photochemical level, the negative effect of the heat-shock treatment was slightly more pronounced in ambient than in elevated CO2-grown plants. A greater tolerance to oxidative stress caused by high temperatures in elevated C02-grown plants, in comparison to ambient CO2 plants, is suggested by the increase in superoxide dismutase activity, after 1 h at 45°C, as well as its relatively high activity after 2 and 4 h of the heat shock in the elevated C02-grown plants in contrast with the decrease to residual levels of superoxide dismutase activity in ambient C02-grown plants immediately after 1 h at 45°C. The observed increase in catalase after 1 h at 45°C in both ambient and elevated C02-grown plants, can be ascribed to the higher rates of photorespiration and respiration under this high temperature.

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf105

Interactive effects of nitrogen and phosphorus on the acclimation potential of foliage photosynthetic properties of cork oak, Quercus suber, to elevated atmospheric CO2 concentrations (Global Change Biology, 1999)
Leaf gas-exchange and chemical composition were investigated in seedlings of Quercus suber L. grown for 21 months either at elevated (700 μmol mol–1) or normal (350 μmol mol–1) ambient atmospheric CO2 concentrations, [CO2], in a sandy nutrient-poor soil with either ‘high’ N (0.3 mol N m–3 in the irrigation solution) or with ‘low’ N (0.05 mol N m–3) and with a constant suboptimal concentration of the other macro- and micronutrients. Although elevated [CO2] yielded the greatest total plant biomass in ‘high’ nitrogen treatment, it resulted in lower leaf nutrient concentrations in all cases, independent of the nutrient addition regime, and in greater nonstructural carbohydrate concentrations. By contrast, nitrogen treatment did not affect foliar N concentrations, but resulted in lower phosphorus concentrations, suggesting that under lower N, P use-efficiency in foliar biomass production was lower. Phosphorus deficiency was evident in all treatments, as photosynthesis became CO2 insensitive at intercellular CO2 concentrations larger than ≈ 300 μmol mol–1, and net assimilation rates measured at an ambient [CO2] of 350 μmol mol–1 or at 700 μmol mol–1 were not significantly different. Moreover, there was a positive correlation of foliar P with maximum Rubisco (Ribulose-1,5-bisphosphate carboxylase/oxygenase) carboxylase activity (Vcmax), which potentially limits photosynthesis at low [CO2], and the capacities of photosynthetic electron transport (Jmax) and phosphate utilization (Pmax), which are potentially limiting at high [CO2]. None of these potential limits was correlated with foliar nitrogen concentration, indicating that photosynthetic N use-efficiency was directly dependent on foliar P availability. Though the tendencies were towards lower capacities of potential limitations of photosynthesis in high [CO2] grown specimens, the effects were statistically insignificant, because of (i) large within-treatment variability related to foliar P, and (ii) small decreases in P/N ratio with increasing [CO2], resulting in balanced changes in other foliar compounds potentially limiting carbon acquisition. The results of the current study indicate that under P-deficiency, the down-regulation of excess biochemical capacities proceeds in a similar manner in leaves grown under normal and elevated [CO2], and also that foliar P/N ratios for optimum photosynthesis are likely to increase with increasing growth CO2 concentrations. Symbols: A, net assimilation rate (μmol m–2 s–1); Amax, light-saturated A (μmol m–2 s–1); α, initial quantum yield at saturating [CO2] and for an incident Q (mol mol–1); [CO2], atmospheric CO2 concentration (μmol mol–1); Ci, intercellular CO2 concentration (μmol mol–1); Ca, CO2 concentration in the gas-exchange cuvette (μmol mol–1); FB, fraction of leaf N in ‘photoenergetics’; FL, fraction of leaf N in light harvesting; FR, fraction of leaf N in Rubisco; Γ*, CO2 compensation concentration in the absence of Rd (μmol mol–1); Jmax*, capacity for photosynthetic electron transport; Jmc, capacity for photosynthetic electron transport per unit cytochrome f (mol e–[mol cyt f]–1 s–1); Kc, Michaelis-Menten constant for carboxylation (μmol mol–1); Ko, Michaelis-Menten constant for oxygenation (mmol mol–1); MA, leaf dry mass per area (g m–2); O, intercellular oxygen concentration (mmol mol–1); [Pi], concentration of inorganic phosphate (mM); Pmax*, capacity for phosphate utilization; Q, photosynthetically active quantum flux density (μmol m–2 s–1); Rd*, day respiration (CO2 evolution from nonphotorespiratory processes continuing in the light); Rubisco, ribulose-1,5-bisphosphate carboxylase/oxygenase; RUBP, ribulose-1,5-bisphosphate; Tl, leaf temperature (°C); UTPU*, rate of triose phosphate utilization; Vcmax*, maximum Rubisco carboxylase activity; Vcr, specific activity of Rubisco (μmol CO2[g Rubisco]–1 s–1] *given in either μmol m–2 s–1 or in μmol g–1 s–1 as described in the text.

Differences in the response of carbon assimilation to summer stress (water deficits, high light and temperature) in four Mediterranean tree species (Physiologia Plantarum, 1998)
Daily changes in photoprotective mechanisms were studied in sun leaves of Quercus suber L., Quercus ilex L., Olea europaea L. and Eucalyptus globulus Labill. trees during the summer in Portugal. Even though stomatal closure explained most of the diurnal variation in carbon assimilation along the summer, a decline in the photochemical yield of photosystem II (F′v/F′m) also occurred, as a result of an excess of intercepted solar radiation when carbon assimilation is limited by stomatal closure due to high vapour pressure deficits and/or soil water deficits. These changes were accompanied by the conversion of violaxanthin to antheraxanthin and zeaxanthin which were correlated with thermal dissipation of excess photon energy. In spite of a common general response, differences between species were observed -Olea europaea, which is a slow-growing tree, had the lowest net photosynthetic rates, the highest proportion of carotenoids in relation to chlorophyll and the highest rates of de-epoxidation of violaxanthin. This enabled a large thermal dissipation of the excess intercepted radiation but led to rather small values of light utilisation for photochemistry (ca 20%). In contrast, in E. globulus, a fast-growing tree, photosynthetic rates were the highest, thermal dissipation of absorbed radiation the lowest and maximal values of light utilisation for photochemistry reached ca 50%. The two Quercus species exhibited an intermediate response. A high degree of co-ordination is apparent between stomatal behaviour, photosynthetic capacity and photoprotection mechanisms.

Photochemical response to summer drought in Quercus ilex trees growing in a naturally CO2 enriched site (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The effect of the interaction between water stress and growth at elevated CO2 on the leaf photochemistry were studied in Quercus ilex trees, growing in a naturally CO2 enriched site (the Bossoleto, Italy). Those plants were compared with plants growing nearby in similar soils but at ambient CO2 concentration. Our data indicate that down-regulation of photosynthesis is lower in non-watered trees from the enriched site than in non-watered trees from the ambient-CO2 site This may be associated to the higher carbon availability for the consumption of the excess absorbed light energy or to an increased protection of the photochemical apparatus against oxidative stress in plants grown under elevated CO2.

Seasonal changes in xanthophyll composition and photosynthesis of cork oak (Quercus suber L.) leaves under mediterranean climate (Journal of Experimental Botany, 1997)
Seasonal changes in pigment composition of sun and shade leaves of cork oak (Quercus suber) were studied under field conditions in Portugal. Expanding leaves showed a high concentration of xanthophyll cycle components, violaxanthin, antheraxanthin and zeaxanthin. The pool of violaxanthin plus antheraxanthin plus zeaxanthin (V+A+Z) varied greatly between the seasons, being higher at the end of summer and in winter when photosynthesis was limited by water stress and cold, respectively. The size of V+A+Z pool was associated to synthesis of zeaxanthin in response to an excess of light. In sun leaves, midday A+Z relative content was positively correlated with the V+A+Z pool, whereas in shade leaves A+Z decreased with leaf ageing. In both leaf types A+Z was positively correlated with the non-photochemical quenching (NPQ) of chlorophyll a fluorescence. However, in winter NPQ did not change significantly throughout the day, whereas the (A+Z)/(V+A+Z) increased following the typical daily trend observed in other seasons.
10.1093/jxb/48.9.1667

Diurnal changes in photoprotective mechanisms in leaves of cork oak (Quercus suber) during summer (Tree Physiology, 1996)
Daily variations in photoprotective mechanisms were studied in sun and shade leaves of 40-year-old cork oak (Quercus suber L.) trees during early summer in Portugal. Although trees were not severely water stressed because predawn leaf water potentials remained high, photosynthesis and stomatal conductance decreased at midday. The midday depression in gas exchange was not reversed by short-term exposure to “optimal” conditions of temperature, light and vapor pressure deficit. Chlorophyll a fluorescence, maximum photochemical yield of photosystem II and the quantum yield of noncyclic electron transport showed midday depressions, but recovered by the evening. Both short-term changes in the components of the xanthophyll cycle (reversible de-epoxidation of violaxanthin during the day) as well as long-term changes (higher xanthophyll content in sun compared with shade leaves) were detected and may play a role in the dissipation of excess energy at midday. Because the activities of enzymes of the antioxidant system, superoxide dismutase and ascorbate peroxidase, were high enough to cope with the increase in oxygen reactive species likely to arise under the stressful conditions of midday, we conclude that these enzymes may provide an additional mechanism for energy dissipation.
10.1093/treephys/16.1-2.115

Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.1755